F0 thoughs and prosodic phrasing: an investigation into the linguistic information contained in a speaker’s baseline when reading - Wichmann, Anne (HERMES - Journal of Language and Communication in Business, 2017)
This paper examines some aspects of the prosody of reading aloud. The pitch contour of a read text was examined, and the low troughs, or valleys, in the contour were identified. The pitch of these troughs, and their position in the text, was found to relate systematically to the structure of the text. This suggests that the speaker’s pitch baseline may carry important linguistic information.